Modulation of intercellular communication by differential regulation and heteromeric mixing of co-expressed connexins - Beyer,E.C. (2000)
Intercellular communication may be regulated by the differential expression of subunit gap junction proteins (connexins) which form channels with differing gating and permeability properties. Endothelial cells express three different connexins (connexin37, connexin40, and connexin43) in vivo. To study the differential regulation of expression and synthesis of connexin37 and connexin43, we used cultured bovine aortic endothelial cells which contain these two connexins in vitro. RNA blots demonstrated discordant expression of these two connexins during growth to confluency. RNA blots and immunoblots showed that levels of these connexins were modulated by treatment of cultures with transforming growth factor-ß1. To examine the potential ability of these connexins to form heteromeric channels (containing different connexins within the same hemi-channel), we stably transfected connexin43-containing normal rat kidney (NRK) cells with connexin37 or connexin40. In the transfected cells, both connexin proteins were abundantly produced and localized in identical distributions as detected by immunofluorescence. Double whole-cell patch-clamp studies showed that co-expressing cells exhibited unitary channel conductances and gating characteristics that could not be explained by hemi-channels formed of either connexin alone. These observations suggest that these connexins can readily mix with connexin43 to form heteromeric channels and that the intercellular communication between cells is determined not only by the properties of individual connexins, but also by the interactions of those connexins to form heteromeric channels with novel properties. Furthermore, modulation of levels of the co-expressed connexins during cell proliferation or by cytokines may alter the relative abundance of different heteromeric combinations.